ChemInform Abstract: S‐Triazene Based Fluorous Coupling Reagent for Direct Amide Synthesis. Issue 30 (July 2015) - Mangawa, Shrawan Kumar; Bagh, Sangram Keshari; Sharma, Kumkum; Awasthi, Satish K.
Abstract Alkyl, benzyl, aryl, and hetaryl carboxylic acids are successfully coupled with primary aliphatic and aromatic amines as well as secondary aliphatic amines.